Pemanfaatan ekstrak daun sirih hijau (piper betle L.) sebagai agen fitoterapi topikal dalam perawatan luka kulit: Tinjauan berdasarkan bukti ilmiah - Nursakinah, Namira Az-Zahra; Rudiyanto, Waluyo; Z, Zahara Nurfatihah; Sibero, Hendra Tarigen (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Skin wounds remain a common health problem in both primary healthcare settings and hospitals due to the high risk of infection, delayed healing, and increased treatment costs. The use of synthetic topical agents in wound care is often associated with side effects and the risk of antimicrobial resistance, prompting the search for safer and more affordable natural-based alternatives. Purpose: To review and synthesize scientific evidence regarding the use of green betel leaf extract (Piper betle L.) as a topical phytotherapeutic agent in the treatment of skin wounds. Method: This systematic literature review was conducted based on PRISMA guidelines. The literature search was conducted through the Scopus database using the keywords